Capacidades para o empreendedorismo internacional no contexto da economia criativa: um estudo na indústria de jogos digitais - Azevedo, Júlia Cardoso de (Universidade do Vale do Rio dos Sinos, 2014)
The creative economy has proved to be an argument for new ventures that have the potential to attend local and global demands. The distinctiveness of this industry lies in the worldwide scope of its activities, which is facilitated by the mobility of talent and/or creativity, non-tangible elements of acting and thinking, which are essential features of these organizations. In the context of digital games industry, this research aimed to analyze the relationship between capabilities and international entrepreneurship in these companies. The theoretical foundation of this research is international entrepreneurship, capabilities needed in this process and creative economy. This literature enabled the elaboration of categories that were used in the construction of data collection instrument and the analysis thereof. The choice of the empirical object was based on a non-systematic observation, that showed that the internationalization of game producers studios as a highlight in the creative economy. For that matter, seven interviews with entrepreneurs and associations were conducted, inspired in the case study technique which increased the understanding of their actions that led to foreign activities, as well as the associated capabilities. The organization of the findings in the previously defined categories highlighted that the international orientation is in the nature of this industry, and that the technical and scientific know-how as well as building networks encourage and facilitate performance in foreign markets. Likewise dynamic and innovative capabilities seem to be a way to follow the characteristic dynamism of this industry. From this, propositions that instigate the continuation of studies on the subject have been built.
Keywords: Empreendedorismo internacional; Capacidades; Economia criativa; Jogos digitais; International entrepreneurship; Capabilities; Creative economy; Digital games; ACCNPQ::Ciências Sociais Aplicadas::Administração